Conductive two-dimensional particle-containing composition, conductive film, and method for producing conductive two-dimensional particle-containing composition
By introducing fluorine atoms and oxygen atoms on the surface of MXene and forming a conductive film with a high dielectric constant, the problems of oxidation and reduced conductivity of MXene materials in air are solved, and the effects of high conductivity and long-term stability are achieved.
Patent Information
- Application Number
- JP2023549419
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-27
- Filing Date
- 2022-08-19
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-08-19
AI Technical Summary
The existing MXene materials are prone to oxidation in air, resulting in a decrease in conductivity. The conductive film formed when solvents such as DMSO are used significantly reduced in conductivity after 6 months.
By introducing fluorine and oxygen atoms on the surface of MXene and using a dielectric with high dielectric constant, such as N-methylformamide (NMF), to form a stable conductive film, improving the conductivity and oxidation resistance of MXene.
The high conductivity and long-term stability of MXene materials are achieved, ensuring that the conductive film maintains high conductivity for a long time, and is suitable for various electronic devices.
Smart Images

Figure 0007670151000005 
Figure 0007670151000001 
Figure 0007670151000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to conductive two-dimensional particle-containing compositions, conductive films, and methods for making conductive two-dimensional particle-containing compositions. [Background technology]
[0002] In recent years, MXene has been attracting attention as a new material having electrical conductivity. MXene is a type of so-called two-dimensional material, and as described below, it is a layered material having the form of one or more layers. In general, MXene has the form of particles of such layered materials (which may include powders, flakes, nanosheets, etc.).
[0003] Currently, various researches are being conducted on the application of MXene to various electric devices. For the above applications, there is a demand for further improving the electrical conductivity of materials containing MXene. As part of the investigations, attempts have been made to improve the properties of MXene by controlling the surface functional groups of MXene. For example, Non-Patent Document 1 shows that by making the surface functional group of MXene one of O, Cl, S, Se, and Te, it is possible to obtain unique structural and electronic properties. In addition, Non-Patent Document 2 shows that (Ti3C2T x It has been shown that MXene can be applied to functional compositions that can be used in various fields such as electrochemical energy storage, smart electronics, and healthcare. x ) Ink with dispersed MXene is shown. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Kamysbayev et al., Covalent surface modifications and superconductivity of two-dimensional metal carbide MXenes: Science 369, 979-983 (2020) [Non-Patent Document 2] Zhang et al., Additive-free MXene inks and direct printing of micro-supercapacitors NATURE COMMUNICATIONS (2019) 10:1795 Summary of the Invention [Problem to be solved by the invention]
[0005] The MXene shown in Non-Patent Document 1 is considered to have a structure that is easily oxidized in air. Therefore, for example, when a conductive film is formed, the conductive film exhibits high conductivity and maintains high conductivity for a long period of time, so that further study of the structure of MXene is considered necessary. In addition, Non-Patent Document 2 discloses a composition in which MXene is dispersed in DMSO or the like, but the conductivity of a conductive film formed using the composition is significantly reduced after 6 months. The present disclosure has been made in consideration of the above circumstances, and its purpose is to provide a composition containing conductive two-dimensional particles (MXene) that exhibits high conductivity when a conductive film is formed and can maintain high conductivity for a long period of time, a conductive film formed from the composition and exhibits high conductivity, and a method for producing a conductive two-dimensional particle-containing composition. [Means for solving the problem]
[0006] According to one aspect of the present disclosure, a conductive two-dimensional particle of a layered material, the particle comprising one or more layers, and a carrier fluid having a dielectric constant greater than that of water; The one or more layers may have the formula: M m Xn (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The conductive two-dimensional particle-containing composition is provided, in which the conductive two-dimensional particle has a fluorine element and an oxygen element.
[0007] According to another aspect of the present disclosure, (a) the formula: M m AX n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; A is at least one Group 12, 13, 14, 15, or 16 element; n is 1 or more and 4 or less, m is greater than n and less than or equal to 5) providing a precursor represented by (b) performing an etching process to remove at least a portion of the A atoms from the precursor using an etching solution; (c) washing the etched product obtained by the etching treatment with water to obtain a water-washed product; (d) performing an intercalation treatment of the intercalation compound, which includes stirring a mixture of the water-washed material and the intercalation compound; (e) Using the intercalation product obtained by the intercalation treatment, delamination and a dispersion medium having a relative dielectric constant greater than that of water are mixed to form a composition. A method for producing a conductive two-dimensional particle-containing composition is provided, comprising: Effect of the Invention
[0008] According to the present disclosure, a conductive two-dimensional particle-containing composition is provided that contains conductive two-dimensional particles formed from a predetermined layered material (also referred to in this specification as "MXene") and having fluorine and oxygen elements, and a dispersion medium having a relative dielectric constant greater than that of water, thereby providing a conductive two-dimensional particle-containing composition that contains MXene, exhibits high conductivity, and can maintain high conductivity for a long period of time, and is useful, for example, for forming a conductive film. [Brief description of the drawings]
[0009] [Figure 1] 1A and 1B are schematic cross-sectional views showing MXene, a layered material that can be used in a conductive two-dimensional particle-containing composition in one embodiment of the present disclosure, where (a) shows a single-layer MXene and (b) shows a multi-layer (exemplarily two-layer) MXene. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Embodiment 1: Conductive two-dimensional particle-containing composition) Hereinafter, a conductive two-dimensional particle-containing composition in one embodiment of the present disclosure will be described in detail, but the present disclosure is not limited to such an embodiment.
[0011] The conductive two-dimensional particle-containing composition in this embodiment is a conductive two-dimensional particle of a layered material, the particle comprising one or more layers, and a carrier fluid having a dielectric constant greater than that of water; The one or more layers may have the formula: M m X n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, and the conductive two-dimensional particles have a fluorine element and an oxygen element. The conductive two-dimensional particle-containing composition contains the conductive two-dimensional particles and a dispersion medium having a relative dielectric constant higher than that of water, and can form, for example, a conductive film having high initial conductivity and suppressed deterioration of the conductivity over time.
[0012] The layered material may be understood as a layered compound, and may be referred to as "M m X n T s ", where s is any number, and conventionally, x or z may be used instead of s. Typically, n can be 1, 2, 3, or 4, but is not limited thereto.
[0013] In the above formula for MXene, M is preferably at least one selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, and Mn, and more preferably at least one selected from the group consisting of Ti, V, Cr, and Mo.
[0014] MXene is a compound represented by the above formula: m X n However, it is known that it can be expressed as follows: Sc2C, Ti2C, Ti2N, Zr2C, Zr2N, Hf2C, Hf2N, V2C, V2N, Nb2C, Ta2C, Cr2C, Cr2N, Mo2C, Mo 1.3 C, Cr 1.3 C, (Ti,V)2C, (Ti,Nb)2C, W2C, W 1.3 C, Mo2N, Nb 1.3 C, Mo 1.3 Y 0.6 C (in the above formula, "1.3" and "0.6" mean approximately 1.3 (= 4 / 3) and approximately 0.6 (= 2 / 3), respectively), Ti3C2, Ti3N2, Ti3(CN), Zr3C2, (Ti,V)3C2, (Ti2Nb)C2, (Ti2Ta)C2, (Ti2Mn)C2, Hf3C2, (Hf2V)C2, (Hf2Mn)C2, (V2Ti)C2, (Cr2Ti)C2, (Cr2V)C 2, (Cr2Nb)C2, (Cr2Ta)C2, (Mo2Sc)C2, (Mo2Ti)C2, (Mo2Zr)C2, (Mo2Hf)C2, (Mo2V)C2, (Mo2Nb)C2, (Mo2Ta)C2, (W2Ti)C2, (W2Zr)C2, (W2Hf)C2, Ti4N3, V4C3, Nb4C3, Ta4C3, (Ti,Nb)4C3, (Nb,Zr)4C3, (Ti2Nb2)C3, (Ti2Ta2)C3, (V2Ti2)C3, (V2Nb2)C3, (V2Ta2)C3, (Nb2Ta2)C3, (Cr2Ti2)C3, (Cr2V 2)C3, (Cr2Nb2)C3, (Cr2Ta2)C3, (Mo2Ti2)C3, (Mo2Zr2)C3, (Mo2Hf2)C3, (Mo2V2)C3, (Mo2Nb2)C3, (Mo2Ta2)C3, (W2Ti2)C3, (W2Zr2)C3, (W2Hf2)C3, (Mo 2.7 V 1.3 ) C3 (In the above formula, "2.7" and "1.3" mean approximately 2.7 (= 8 / 3) and approximately 1.3 (= 4 / 3), respectively.)
[0015] Typically, in the above formula, M can be titanium or vanadium, and X can be a carbon atom or a nitrogen atom. For example, the MAX phase, which is a precursor of MXene, is Ti3AlC2, and MXene is Ti3C2T s (In other words, M is Ti, X is C, n is 2, and m is 3).
[0016] In this embodiment, MXene may contain a relatively small amount of residual A atoms, for example, 10 mass% or less of the original A atoms. The amount of residual A atoms may be preferably 8 mass% or less, more preferably 6 mass% or less. However, even if the amount of residual A atoms exceeds 10 mass%, there may be cases where there is no problem depending on the application and use conditions of the electrode.
[0017] Hereinafter, the conductive two-dimensional particles (also referred to as "MXene particles") in the conductive two-dimensional particle-containing composition according to this embodiment will be described with reference to FIG.
[0018] The conductive two-dimensional particle of this embodiment is an aggregate including one layer of MXene10a (single-layer MXene) as illustrated in FIG. 1(a). More specifically, MXene10a is m X n The layer body (M m X n The MXene layer 7a has a layer body 1a and a modification or termination T3a, 5a present on the surface of the layer body 1a (more specifically, on at least one of the two surfaces facing each other in each layer). m X n T s ", where s is any number.
[0019] The layered material particles according to the present embodiment may include multiple layers as well as one layer. As an example of multiple layer MXene (multilayer MXene), as shown in FIG. 1(b), two layers of MXene 10b are included, but are not limited to these examples. In FIG. 1(b), 1b, 3b, 5b, and 7b are the same as 1a, 3a, 5a, and 7a in FIG. 1(a). The two adjacent MXene layers (e.g., 7a and 7b) of the multilayer MXene do not necessarily have to be completely separated, and may be partially in contact. The MXene 10a is a single layer in which the multilayer MXene 10b is individually separated, and the unseparated multilayer MXene 10b may remain, resulting in a mixture of the single layer MXene 10a and the multilayer MXene 10b. Even when the multilayer MXene is included, the multilayer MXene is preferably an MXene with a small number of layers obtained through a delamination process. The "small number of layers" refers to, for example, 10 or less layers of MXene. Hereinafter, this "multilayer MXene with a small number of layers" may be referred to as "few-layer MXene." The thickness of the few-layer MXene in the stacking direction is preferably 15 nm or less, and more preferably 10 nm or less. Furthermore, the single-layer MXene and few-layer MXene may be collectively referred to as "single-layer / few-layer MXene."
[0020] The particles of the layered material according to the present embodiment preferably contain a large amount of single-layered and few-layered MXene. By containing a large amount of single-layered and few-layered MXene, the specific surface area of MXene can be made larger than that of multi-layered MXene, and as a result, as shown in the examples described later, the deterioration of electrode properties over time can be further suppressed. For example, the particles of the layered material according to the present embodiment preferably contain single-layered and few-layered MXene, which has 10 or less MXene layers and a thickness of 15 nm or less, preferably 10 nm or less, and the ratio of the single-layered and few-layered MXene to the total MXene is 80% or more by volume, more preferably 90% or more by volume, and even more preferably 95% or more by volume. It is also more preferable that the volume of the single-layered MXene is larger than the volume of the few-layered MXene. Since the true density of these MXenes does not vary significantly depending on the form of existence, it can be said that it is more preferable that the mass of the single-layered MXene is larger than the mass of the few-layered MXene. When these relationships are satisfied, the specific surface area can be further increased, and the deterioration of the electrical conductivity over time can be further suppressed. Most preferably, the particles of the layered material according to this embodiment are formed only of a single layer of MXene.
[0021] Although not limiting this embodiment, the thickness of each layer of MXene (corresponding to the above-mentioned MXene layers 7a and 7b) can be, for example, 1 nm or more and 30 μm or less, and may be, for example, 1 nm or more and 5 nm or less, or even 1 nm or more and 3 nm or less (which can vary mainly depending on the number of M atomic layers contained in each layer). For each stack of multilayer MXene that can be included, the interlayer distance (or gap dimension, shown as Δd in FIG. 1(b)) can be, for example, 0.8 nm or more and 10 nm or less, particularly 0.8 nm or more and 5 nm or less, more particularly about 1 nm, and the total number of layers can be 2 or more and 20,000 or less.
[0022] (Fluorine and oxygen elements) The conductive two-dimensional particles have fluorine and oxygen elements on the surface. Having fluorine and oxygen means that these elements are bonded and adsorbed on the surface of MXene, for example, in the form of ions. The conductive two-dimensional particles have fluorine and oxygen elements with small atomic radii. For example, the presence of oxygen and fluorine elements with small atomic radii on the surface of the layer body constituting MXene narrows the interlayer distance, stabilizes the structure, and increases oxidation resistance. Furthermore, moisture absorption due to the insertion of water molecules between the layers is suppressed, and high moisture absorption resistance can be achieved. The presence of the fluorine and oxygen atoms in the conductive two-dimensional particles can be confirmed by the XPS method, as described below.
[0023] (chlorine, phosphate, iodine and sulfate ions) The conductive two-dimensional particle is characterized in that the modification or termination T contains a chlorine atom or the layer M and PO4 3- , I and SO4 2- The chlorine atom, PO4 3- , I and SO4 2- may originate from the raw materials used in the manufacturing process of the conductive two-dimensional particles. The chlorine atom, I, may be present in the form of an ion. As described above, the modification or terminal T contains a chlorine atom or the M of the layer and PO4 3- , I and SO4 2- By bonding with at least one selected from the group consisting of, monolayering is easily caused during the manufacturing process of the conductive two-dimensional particles, and a composition containing more monolayer / few-layer MXene is obtained as the conductive two-dimensional particles. This is preferable because a conductive film with higher conductivity can be obtained as the conductive film formed using the composition. The presence of these chlorine atoms, etc. on the surface of the conductive two-dimensional particles can be confirmed by the XPS method as described below.
[0024] The proportion of the conductive two-dimensional particles (MXene content) contained in the conductive two-dimensional particle-containing composition is not particularly limited. For example, in order to form a thick conductive film, the MXene content in the composition may be 1 mass% or more in terms of solid content. The conductive two-dimensional particles are difficult to disperse, and it is difficult to form a composition. However, according to the conductive two-dimensional particle-containing composition of this embodiment, the conductive two-dimensional particles are easily dispersed in a dispersion medium having a relative dielectric constant greater than that of water, so that a composition with a high dispersion rate of the conductive two-dimensional particles can be formed. By using a composition with such a high dispersion rate, for example, in film formation, a conductive film that requires a thickness, such as for electrode applications, can be produced with good productivity. The proportion of the conductive two-dimensional particles can also be 0.01 mass% or more in terms of solid content. The proportion of the conductive two-dimensional particles can also be 1.5 mass% or more in terms of solid content. In addition, taking into account the dispersibility of the conductive two-dimensional particles, the upper limit of the above proportion is, for example, 10 mass% in terms of solid content.
[0025] (dispersion medium) The conductive two-dimensional particle-containing composition according to the present embodiment uses a dispersion medium having a dielectric constant greater than that of water as a dispersion medium for dispersing the conductive two-dimensional particles. In a dispersion medium having a dielectric constant greater than that of water, the charge of the conductive two-dimensional particles (MXene particles) becomes more stable, resulting in higher dispersibility. Due to the high dispersion stability, a conductive two-dimensional particle-containing composition can be realized in which the conductive two-dimensional particles (MXene particles) are dispersed at a high content without aggregation. By forming a film using this highly dispersed conductive two-dimensional particle-containing composition, for example, a conductive film exhibiting high orientation and high conductivity can be realized. The dielectric constant of water is 80.4 at 20°C, and the dispersion medium for dispersing the conductive two-dimensional particles only needs to be larger than the dielectric constant of water at 20°C. For example, a dispersion medium having a dielectric constant greater than 80, or even 100 or more, can be used. Hereinafter, a dispersion medium having a dielectric constant greater than that of water may be referred to as a "high dielectric constant dispersion medium."
[0026] Examples of dispersion media having a dielectric constant greater than that of water include N-methylformamide (NMF, dielectric constant: 171) and N-methylacetamide (NMAc, dielectric constant: 179), and one or more of these can be used.
[0027] In this embodiment, if the relative dielectric constant is larger than that of water, a mixed dispersion medium of a high relative dielectric constant dispersion medium and another dispersion medium may be used. A preferred dispersion medium includes at least one of N-methylformamide and N-methylacetamide, which are high relative dielectric constant dispersion media. More preferably, the dispersion medium includes at least one of N-methylformamide and N-methylacetamide in an amount of 50% by volume or more. Other dispersion media include dispersion media with a relative dielectric constant of 10 or more, such as aqueous dispersion media and organic dispersion media. A representative aqueous dispersion medium is water, and in some cases, an aqueous solution including water and a relatively small amount of other liquid substances (for example, 30% by mass or less, preferably 20% by mass or less on a total basis) may be used. Examples of organic dispersion media include acetonitrile (dielectric constant: 38), N,N-dimethylacetamide (dielectric constant: 38), N,N-dimethylformamide (dielectric constant: 37), DMSO (dielectric constant: 47), DMF (dielectric constant: 37), NMP (dielectric constant: 32), acetone (dielectric constant: 20), 2-methyl-2-propanol (dielectric constant: 10), isopropyl alcohol (dielectric constant: 18), ethanol (dielectric constant: 25) and alcohol including methanol (dielectric constant: 33). As a dispersion medium having a higher dielectric constant than water, it is preferable to include NMF having a high dielectric constant, and most preferably, the dispersion medium is composed of NMF.
[0028] (Additives) The conductive two-dimensional particle-containing composition according to this embodiment may contain additives such as amines such as tetramethylammonium hydroxide, hexylamine, octylamine, etc., polyphosphoric acid, sodium ascorbate, etc., in addition to the conductive two-dimensional particles and the dispersion medium. The proportion of the additive in the composition is not particularly limited, but from the viewpoint of increasing the concentration of the conductive two-dimensional particles, the proportion of the additive in the composition is suppressed to, for example, 10 mass% or less.
[0029] (Form of composition) The conductive two-dimensional particle-containing composition according to this embodiment may be, for example, an ink, a paste, or a slurry.
[0030] As an embodiment of the paste, a conductive paste of a composite material containing a polymer can be mentioned. The mass ratio of the conductive two-dimensional particles (particles of a layered material) in the conductive paste can be, for example, 50% or more. As the polymer, for example, a hydrophilic polymer (including a hydrophobic polymer with a hydrophilic auxiliary to exhibit hydrophilicity, and a hydrophobic polymer or the like that has been subjected to a hydrophilization treatment on the surface) can be mentioned. As the hydrophilic polymer, more preferably, one or more selected from the group consisting of polysulfone, cellulose acetate, regenerated cellulose, polyethersulfone, water-soluble polyurethane, polyvinyl alcohol, sodium alginate, acrylic acid-based water-soluble polymer, polyacrylamide, polyaniline sulfonic acid, and nylon can be included.
[0031] The hydrophilic polymer is more preferably a hydrophilic polymer having a polar group, the polar group being a group that modifies the layer or forms a hydrogen bond with the terminal T. As the polymer, for example, one or more types of polymers selected from the group consisting of water-soluble polyurethane, polyvinyl alcohol, sodium alginate, acrylic acid-based water-soluble polymer, polyacrylamide, polyaniline sulfonic acid, and nylon are preferably used.
[0032] Among these, one or more polymers selected from the group consisting of water-soluble polyurethane, polyvinyl alcohol, and sodium alginate are more preferable. As the polymer, a polymer having a urethane bond that has both hydrogen bond donor and hydrogen bond acceptor properties is preferable, and from that viewpoint, the water-soluble polyurethane is particularly preferable.
[0033] (Embodiment 2: Method for producing a composition containing conductive two-dimensional particles) Hereinafter, a method for producing a conductive two-dimensional particle-containing composition according to an embodiment of the present invention will be described in detail, but the present disclosure is not limited to this embodiment.
[0034] The method for producing the conductive two-dimensional particle-containing composition of the present embodiment includes the steps of: (a) the formula: M m AX n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; A is at least one Group 12, 13, 14, 15, or 16 element; n is 1 to 4, m is greater than n and less than or equal to 5) providing a precursor represented by (b) performing an etching process to remove at least a portion of the A atoms from the precursor using an etching solution; (c) washing the etched product obtained by the etching treatment with water to obtain a water-washed product; (d) performing an intercalation treatment of the intercalation compound, which includes stirring a mixture of the water-washed material and the intercalation compound; (e) forming a composition by using the intercalation treatment product obtained by the intercalation treatment, performing delamination and mixing with a dispersion medium having a relative dielectric constant greater than that of water; This manufacturing method makes it possible to manufacture a conductive two-dimensional particle-containing composition that is optimal for manufacturing a conductive film or the like that can maintain high conductivity for a long period of time.
[0035] Each step of the above manufacturing method will now be described in detail. ·Process (a) First, a predetermined precursor is prepared. The predetermined precursor that can be used in this embodiment is the MAX phase, which is a precursor of MXene. The following formula: M m AX n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; A is at least one Group 12, 13, 14, 15, or 16 element; n is 1 to 4, m is greater than n and less than or equal to 5) It is expressed as:
[0036] The above M, X, n, and m are as described for MXene. A is at least one element of Groups 12, 13, 14, 15, and 16, and is usually an A group element, typically Groups IIIA and IVA, and more specifically may include at least one element selected from the group consisting of Al, Ga, In, Tl, Si, Ge, Sn, Pb, P, As, S, and Cd, and is preferably Al.
[0037] The MAX phase is M m X n (each X may have a crystal lattice in which it is located in the octahedral array of M) between which a layer composed of A atoms is located. In the MAX phase, typically when m=n+1, one layer of X atoms is arranged between each of the n+1 layers of M atoms (collectively referred to as "M m X n and a layer of A atoms (also referred to as an "A atom layer") arranged as a layer next to the n+1th layer of M atoms, but is not limited thereto.
[0038] The MAX phase can be produced by a known method. For example, TiC powder, Ti powder, and Al powder are mixed in a ball mill, and the resulting mixed powder is sintered in an Ar atmosphere to obtain a sintered body (a block-shaped MAX phase). The sintered body is then pulverized with an end mill to obtain a powdered MAX phase for the next process.
[0039] ·Process (b) Etching is performed by using an etching solution to remove at least some of the A atoms from the precursor. The etching solution preferably contains one or more of HF, H3PO4, HCl, HI, and H2SO4. The etching solution more preferably contains at least one of HF (hydrofluoric acid) and H3PO4 (phosphoric acid). For example, etching can be performed by the so-called MILD method in which HCl and LiF contained in the etching solution are reacted in the system to generate HF, but it is preferable to perform etching by the so-called ACID method in which etching is performed with an etching solution containing HF (hydrofluoric acid) or an etching solution containing phosphoric acid. These methods are preferable because they can easily obtain flake-shaped layered material particles (MXene particles) with a large planar area and a number average Feret diameter of preferably 3 μm or more compared to the MILD method. Other conditions for etching are not particularly limited, and known conditions can be adopted. As the etching solution, a mixture of the above-mentioned acid and, for example, pure water as a solvent can be used. The etching solution may be one that satisfies at least one of the following: HF concentration 1.5M or more and 14M or less, H3PO4 concentration 5.5M or more, HCl concentration 6.0M or more, HI concentration 5.0M or more, and H2SO4 concentration 5.0M or more. In the etching of the A atoms, in addition to the A atoms, some of the M atoms may also be selectively etched in some cases. An example of the etched product obtained by the above etching is a slurry.
[0040] ·Process (c) The etched product obtained by the etching is washed with water. By washing with water, the acid used in the etching can be sufficiently removed. The amount of water to be mixed with the etched product and the washing method are not particularly limited. For example, water is added and stirring, centrifugation, etc. are performed. Examples of the stirring method include stirring using a hand shake, an automatic shaker, a shear mixer, a pot mill, etc. The degree of stirring, such as the stirring speed and stirring time, may be adjusted according to the amount and concentration of the object to be treated. The washing with water may be performed one or more times. Preferably, the washing with water is performed multiple times. For example, specifically, steps (i) to (iv) of (i) adding water (to the etched product or the remaining precipitate obtained in (iii) below), (ii) stirring, (iii) centrifuging the stirred product, and (iv) discarding the supernatant after centrifugation and recovering the remaining precipitate may be performed two or more times, for example, 15 times or less.
[0041] ·Process (d) Intercalation of the intercalation compound is carried out, which includes a step of stirring a mixture obtained by mixing the treated product (water-washed product) obtained by the water washing with the intercalation compound of the water-washed product.
[0042] The intercalation compound of the water-treated product may be of any type, so long as it can be inserted between the layers of the water-treated product and separated into each layer by the delamination in the next step (e). The intercalation compound is preferably an alkali metal compound or an alkaline earth metal compound. More preferably, it is a Li-containing compound. As the Li-containing compound, an ionic compound in which Li ions and cations are bonded can be used. For example, halides including iodides, chlorides, and fluorides, hydroxides, phosphates, sulfides including sulfates, nitrates, acetates, carboxylates, etc. of Li ions can be mentioned.
[0043] The content of the intercalation compound in the intercalation blend is preferably 0.001% by mass or more. The content is more preferably 0.01% by mass or more, and even more preferably 0.1% by mass or more. On the other hand, from the viewpoint of dispersibility in the solution, the content of the intercalation compound is preferably 10% by mass or less, and more preferably 1% by mass or less.
[0044] The specific method of intercalation is not particularly limited, and for example, the intercalation compound may be mixed with the water medium clay of the MXene, and stirred or left to stand. For example, stirring at room temperature may be used. Examples of the stirring method include a method using a stirrer or other stirring bar, a method using a stirring blade, a method using a mixer, and a method using a centrifugal device. The stirring time can be set according to the manufacturing scale of the electrode, and may be set, for example, between 12 and 24 hours.
[0045] ·Process (e) The intercalation product obtained by the intercalation treatment in step (d) is used to perform delamination and mixing with a dispersion medium having a relative dielectric constant greater than that of water, thereby forming a composition.
[0046] The above-mentioned delamination can make the MXene into a single layer or a few layers. For example, stirring methods include stirring using hand shake, an automatic shaker, etc. The degree of stirring, such as the stirring speed and stirring time, may be adjusted according to the amount and concentration of the material to be treated. In the manufacturing method of this embodiment, ultrasonic treatment is not performed as delamination. As described above, since ultrasonic treatment is not performed, particle destruction is unlikely to occur, and as a result, single-layered or few-layered MXene can be obtained as particles of the layered material, which have a large plane parallel to the particle layer, i.e., a large two-dimensional surface, and a large number average Feret diameter.
[0047] The dispersion medium having a relative dielectric constant higher than that of water used for mixing is as described above for the dispersion medium having a relative dielectric constant higher than that of water contained in the conductive two-dimensional particle-containing composition.
[0048] In the method for producing a conductive two-dimensional particle-containing composition according to the present embodiment, the specific embodiments of the steps (d) and (e) may take the following modes (I), (II), and (III) as multiple modes. Modes (I), (II), and (III) are described below. (I) In step (d), the mixture of the water-washed material and the intercalation compound is made alkaline, and in step (e), the intercalation-treated material is mixed with a dispersion medium having a dielectric constant higher than that of water, thereby simultaneously carrying out delamination and mixing with a dispersion medium having a dielectric constant higher than that of water. (II) In step (d), the mixture of the water-washed product and the intercalation compound is acidified, and in step (e), the intercalation-treated product is delaminated, and then the delamination-treated product obtained by the delamination is mixed with a dispersion medium having a dielectric constant greater than that of water to form a composition. (III) In step (d), the mixture of the water-washed material and the intercalation compound is acidified, and in step (e), the intercalation-treated material is mixed with a dispersion medium having a dielectric constant higher than that of water, thereby simultaneously carrying out delamination and mixing with a dispersion medium having a dielectric constant higher than that of water.
[0049] In the above embodiment (I), the mixed solution of the water-washed product and the intercalation compound in the step (d) may be alkaline. For example, the pH may be in the range of 8 to 14. The method for making the mixed solution alkaline is not limited. For example, the mixed solution may contain a hydroxide as the intercalation compound, preferably lithium hydroxide as the Li-containing compound. Alternatively, the mixed solution may contain a hydroxide such as ammonia, potassium hydroxide, sodium hydroxide, calcium hydroxide, or magnesium hydroxide as a pH adjuster.
[0050] In the above-mentioned aspects (I) and (III), in step (e), the intercalation-treated product is mixed with a dispersion medium having a dielectric constant greater than that of water, and delamination and mixing of the dispersion medium having a dielectric constant greater than that of water are performed simultaneously. For example, as shown in the examples described later, the intercalation-treated product is mixed with a dispersion medium having a dielectric constant greater than that of water to obtain a mixture for stirring. The mixture for stirring may contain the intercalation-treated product in a ratio of 0.1 g to 10 g in terms of solid content per 1 mL to 100 mL of dispersion medium (at this ratio, both the solid content of the dispersion medium and the intercalation-treated product are increased). The mixture for stirring may be stirred at 20 to 25°C (room temperature). The stirred product obtained by stirring can be further stirred using, for example, a handshake, an automatic shaker, a stirrer, a stirring blade, or the like, and then centrifuged in a centrifuge to recover the supernatant. The resulting supernatant can then be centrifuged again, after which the supernatant is discarded, and the remaining precipitate can be obtained as a composition containing highly dispersed conductive two-dimensional particles.
[0051] In the above-mentioned embodiment (II) and embodiment (III), the mixed solution of the water-washed product and the intercalation compound in the step (d) may be acidic. For example, the pH may be in the range of 0 to 6. The method of making the mixed solution acidic is not limited. For example, the mixed solution may be prepared by containing a chloride as the intercalation compound, preferably lithium chloride as the Li-containing compound. Alternatively, the mixed solution may be prepared by containing the intercalation compound and an inorganic acid such as hydrochloric acid, phosphoric acid, or sulfuric acid as a pH adjuster.
[0052] In the above aspect (II), in step (e), the intercalation-treated product is delaminate using an aqueous dispersion medium, and then the delamination-treated product obtained by the delamination is mixed with a dispersion medium having a relative dielectric constant greater than that of water to form a composition.
[0053] The delamination includes stirring the treated product obtained by the intercalation in step (d) in an aqueous dispersion medium such as pure water. For example, the slurry after the intercalation is centrifuged to discard the supernatant, and then pure water is added to the remaining precipitate, followed by stirring, for example, by hand shaking or an automatic shaker, followed by centrifugation to collect the supernatant, and this is repeated. The collected supernatant is then centrifuged, and the resulting supernatant is discarded, to obtain a clay-like single-layered or few-layered MXene as the delamination treated product.
[0054] After the delamination, the delamination treatment product is stirred in a dispersion medium having a dielectric constant greater than that of water. The stirring treatment product obtained by stirring can be further stirred by using, for example, a hand shake, an automatic shaker, a wet disperser, ultrasonic waves, etc., then centrifuged with a centrifuge to collect the supernatant, then centrifuged the obtained supernatant, discarded the supernatant, and obtained the remaining precipitate as a conductive two-dimensional particle-containing composition with a high dispersion ratio.
[0055] (Embodiment 3: Conductive film formed from a composition containing conductive two-dimensional particles) This embodiment includes a conductive film obtained by using a conductive two-dimensional particle-containing composition. The conductive film formed by the conductive two-dimensional particle-containing composition has high orientation and shows high conductivity. The conductive film formed by the conductive two-dimensional particle-containing composition of this embodiment can achieve a conductivity of, for example, 5000 S / cm or more, calculated by substituting the thickness of the conductive film measured by a micrometer, a scanning electron microscope (SEM), or a stylus-type surface profiler and the surface resistivity of the conductive film measured by a four-probe method into the following formula: Conductivity [S / cm] = 1 / (Thickness of conductive film [cm] × Surface resistivity of conductive film [Ω / □])
[0056] The method of forming the conductive film is not limited, and examples thereof include filtration, coating, immersion, and the like. Examples of the filtration method include suction filtration of the composition. For example, a membrane filter (Durapore, manufactured by Merck Ltd., pore size 0.45 μm) can be used as the filter for suction filtration. Examples of the coating method include spray coating using a nozzle such as a one-fluid nozzle, a two-fluid nozzle, or an airbrush, slit coating using a table coater, a comma coater, or a bar coater, screen printing, metal mask printing, spin coating, immersion, brushing, and dripping.
[0057] The above coating and drying may be repeated several times as necessary until a conductive film of the desired thickness is obtained. Drying and curing can be performed, for example, at a temperature of 80° C. or higher and 400° C. or lower using a normal pressure oven or a vacuum oven.
[0058] The obtained conductive film can be used in applications requiring high conductivity (reducing the decrease in initial conductivity and preventing oxidation), such as electrodes and electromagnetic shields (EMI shields) in any suitable electrical device. The electrodes are not particularly limited, and can be, for example, capacitor electrodes, battery electrodes, biosignal sensing electrodes, sensor electrodes, antenna electrodes, and the like. By using the conductive film of this embodiment, it is possible to obtain large-capacity capacitors and batteries, low-impedance biosignal sensing electrodes, and highly sensitive sensors and antennas, even in a smaller volume (volume occupied by the device). EXAMPLES
[0059] [Preparation of monolayer MXene] [Examples 1 to 5] In Examples 1 to 5, the MXene-containing compositions were prepared by carrying out the following steps in order: (1) preparation of precursor (MAX), (2) etching of the precursor, (3) cleaning after etching, (4) intercalation of Li, and (5) delamination and mixing of a high-dielectric-constant dispersion medium, as described in detail below. That is, in Examples 1 to 5, the dispersion medium was replaced from water to a specified dispersion medium before the formation of a monolayer of MXene.
[0060] (1) Preparation of precursor (MAX) TiC powder, Ti powder, and Al powder (all manufactured by Kojundo Chemical Laboratory Co., Ltd.) were mixed in a 2:1:1 molar ratio in a ball mill containing zirconia balls for 24 hours. The mixed powder was sintered at 1350°C for 2 hours in an Ar atmosphere. The sintered body (block-shaped MAX) was pulverized with an end mill to a maximum dimension of 40 μm or less. As a result, Ti3AlC2 particles were obtained as a precursor (powder-shaped MAX).
[0061] (2) Etching of Precursor Using the Ti3AlC2 particles (powder) prepared by the above method, etching was carried out under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components derived from the Ti3AlC2 powder. (Etching conditions) Precursor: Ti3AlC2 (passed through a 45μm sieve) Etching solution composition: 49% HF and HO in the amounts shown in Table 1 below Precursor input: 3.0g Reaction vessel: 100mL Eye Boy Etching temperature: 35℃ Etching time: 24h Stirrer speed: 400 rpm
[0062] [Table 1]
[0063] (3) Cleaning after etching The above slurry was divided into two equal parts and placed in two 50 mL centrifuge tubes. The slurry was then centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded. After that, (i) 35 mL of pure water was added to the remaining precipitate in each centrifuge tube, (ii) the mixture was stirred by hand shaking, (iii) the mixture was centrifuged at 3500 G for 5 minutes, and (iv) the supernatant was removed. These steps (i) to (iv) were repeated a total of 10 times. Finally, the mixture was centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded to obtain Ti3C2T. s - Moisture medium clay was obtained.
[0064] (4) Lithium intercalation Ti3C2T prepared by the above method s -The clay was stirred under the following conditions to intercalate the Li ions. (Li intercalation conditions) · Ti3C2T s - Moisture medium clay (MXene after washing): 0.75g solids ·Pure water: 20mL Li ion source: 15mL of pure water + 0.75g of LiOH Reaction vessel: 100mL Eye Boy ·Temperature: 20~25℃ (room temperature) Mixing time: 18 hours Stirring speed: 700 rpm
[0065] After the above stirring, the stirred product was transferred to a 50 mL centrifuge tube and centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded. Then, (i) 35 mL of pure water was added to the remaining precipitate, (ii) the mixture was stirred by hand shaking, (iii) the mixture was centrifuged at 3500 G for 5 minutes, and (iv) the supernatant was removed. These steps (i) to (iv) were repeated a total of five times. Finally, the mixture was centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded to obtain a water-washed product.
[0066] (5) Delamination and mixing of high dielectric constant dispersion medium The delamination and mixing of the high dielectric constant dispersion medium were carried out by stirring under the following conditions. (Conditions for delamination and mixing of high dielectric constant dispersion medium) The water-washed material (MXene after intercalation): solids content 0.75g Dispersion medium: 30 mL of NMF in Examples 1 to 4 and 30 mL of NMAc in Example 5 Reaction vessel: 100mL Eye Boy ·Temperature: 20~25℃ (room temperature) Mixing time: 18 hours Stirring speed: 700 rpm
[0067] After the stirring was completed, the mixture was stirred for 15 minutes on a shaker, and then centrifuged at 3500G for 5 minutes using a centrifuge to recover the supernatant containing the monolayered MXene.Then, the obtained supernatant was centrifuged at 10000G for 2 hours using a centrifuge to discard the supernatant, and the remaining precipitate was obtained as a composition containing conductive two-dimensional particles with a high dispersion ratio.
[0068] [Examples 6 to 9] In Examples 6 to 9, the MXene-containing compositions were prepared by carrying out the following steps in order: (1) preparation of precursor (MAX), (2) etching of the precursor, (3) cleaning after etching, (4) Li intercalation, (5) delamination, and (6) mixing of a high dielectric constant dispersion medium, as described in detail below. That is, in Examples 6 to 9, after the formation of a monolayer of MXene, the dispersion medium was replaced from water to a specified dispersion medium.
[0069] (1) Preparation of precursor (MAX) TiC powder, Ti powder, and Al powder (all manufactured by Kojundo Chemical Laboratory Co., Ltd.) were mixed in a 2:1:1 molar ratio in a ball mill containing zirconia balls for 24 hours. The mixed powder was sintered at 1350°C for 2 hours in an Ar atmosphere. The sintered body (block-shaped MAX) was pulverized with an end mill to a maximum dimension of 40 μm or less. As a result, Ti3AlC2 particles were obtained as a precursor (powder-shaped MAX).
[0070] (2) Etching of Precursor Using the Ti3AlC2 particles (powder) prepared by the above method, etching was carried out under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components derived from the Ti3AlC2 powder. (Etching conditions) Precursor: Ti3AlC2 (passed through a 45μm sieve) Etching solution composition: Acid of the type and amount shown in Table 2 below, 49% HF of the amount shown in Table 2 below, and H2O (As acids, HCl with a concentration of 35-37%, HI with a concentration of 55-57%, H3PO4 with a concentration of 85%, and H2SO4 with a concentration of 98% are used.) Precursor input: 3.0g Reaction vessel: 100mL Eye Boy Etching temperature: 35℃ Etching time: 24h Stirrer speed: 400 rpm
[0071] [Table 2]
[0072] (3) Cleaning after etching The above slurry was divided into two equal parts and placed in two 50 mL centrifuge tubes. The slurry was then centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded. After that, (i) 35 mL of pure water was added to the remaining precipitate in each centrifuge tube, (ii) the mixture was stirred by hand shaking, (iii) the mixture was centrifuged at 3500 G for 5 minutes, and (iv) the supernatant was removed. These steps (i) to (iv) were repeated a total of 10 times. Finally, the mixture was centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded to obtain Ti3C2T. s - Moisture medium clay was obtained.
[0073] (4) Lithium intercalation Ti3C2T prepared by the above method s-The clay was stirred under the following conditions to intercalate the Li ions. (Li intercalation conditions) · Ti3C2T s - Moisture medium clay (MXene after washing): 0.75g solids ·Pure water: 20mL Li ion source: Pure water (H2O) in the amount shown in Table 3 below, and Li salts and acids of the types and amounts shown in Table 3 below. Reaction vessel: 100mL Eye Boy ·Temperature: 20~25℃ (room temperature) Mixing time: 18 hours Stirring speed: 700 rpm
[0074] [Table 3]
[0075] After the stirring was completed, the stirred product was transferred to a 50 mL centrifuge tube and centrifuged at 3500 G for 5 minutes using a centrifuge. The supernatant was then discarded to obtain a Li-intercalated product (MXene clay).
[0076] (5) Delamination 35 mL of pure water was added to the Li intercalation product (MXene clay). Next, after stirring for 15 minutes on a shaker, centrifugation was performed using a centrifuge at 3500G for 5 minutes. The supernatant was collected as a single-layered MXene-containing solution. (i) 35 mL of pure water was added again to the remaining precipitate, (ii) after stirring for 15 minutes on a shaker, centrifugation was performed using a centrifuge at 3500G for 5 minutes to collect the supernatant again. These operations (i) and (ii) were performed a total of five times. The obtained supernatant was then centrifuged using a centrifuge at 4300G for 2 hours, and the precipitate was collected as a single-layered MXene-containing clay.
[0077] (6) Mixing of high dielectric constant dispersion medium NMF was added as a high dielectric constant dispersion medium to the monolayered MXene-containing clay prepared by the above method under the following conditions, and the mixture was stirred to obtain a composition. - Monolayered MXene-containing clay: 0.75g solid content ·Dispersion medium: NMF 30mL Reaction vessel: 100mL Eye Boy ·Temperature: 20~25℃ (room temperature) Mixing time: 18 hours Mixing: 700rpm
[0078] After the stirring was completed, the mixture was stirred for 15 minutes on a shaker, and then centrifuged at 3500G for 5 minutes using a centrifuge to recover the supernatant containing the monolayered MXene.Then, the obtained supernatant was centrifuged at 10000G for 2 hours using a centrifuge to discard the supernatant, and the remaining precipitate was obtained as a composition containing conductive two-dimensional particles with a high dispersion ratio.
[0079] [Comparative Examples 1 and 2] In Comparative Examples 1 and 2, MXene-containing compositions were prepared by carrying out, in order, (1) preparation of a precursor (MAX), (2) etching of the precursor, (3) cleaning after etching, and (4) replacement of the dispersion medium, with reference to the manufacturing conditions described in Non-Patent Document 2, which will be described in detail below.
[0080] (1) Preparation of precursor (MAX) TiC powder, Ti powder, and Al powder (all manufactured by Kojundo Chemical Laboratory Co., Ltd.) were mixed in a 2:1:1 molar ratio in a ball mill containing zirconia balls for 24 hours. The mixed powder was sintered at 1350°C for 2 hours in an Ar atmosphere. The sintered body (block-shaped MAX) was pulverized with an end mill to a maximum dimension of 40 μm or less. As a result, Ti3AlC2 particles were obtained as a precursor (powder-shaped MAX).
[0081] (2) Etching of Precursor Using the Ti3AlC2 particles (powder) prepared by the above method, etching was carried out under the following etching conditions to obtain a solid-liquid mixture (slurry) containing solid components derived from the Ti3AlC2 powder. (Etching conditions) Precursor: Ti3AlC2 (passed through a 45μm sieve) Etching solution composition: 23 mL of HCl (concentration: 35-37%), 3.0 g of LiF, 7 mL of H2O Precursor input: 3.0g Reaction vessel: 100mL Eye Boy Etching temperature: 35℃ Etching time: 24h Stirrer speed: 400 rpm
[0082] (3) Cleaning after etching The above slurry was divided into two equal parts and placed in two 50 mL centrifuge tubes. Then, the slurry was centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded. After that, (i) 35 mL of pure water was added to the remaining precipitate in each centrifuge tube, (ii) the precipitate was stirred by hand shaking, and the supernatant was discarded. This (i) and (ii) were repeated 10 times. Finally, the slurry was centrifuged at 3500 G for 5 minutes using a centrifuge, and the supernatant was discarded to obtain Ti3C2T. s - Moisture medium clay was obtained.
[0083] (4) Replacement of dispersion medium Ti3C2T with a solid content of 0.1g s-20 mL of dispersion medium (DMSO in Comparative Example 1, DMF in Comparative Example 2) was added to the water medium clay, stirred by hand shaking, and the supernatant was discarded. Then, centrifugation was performed using a centrifuge at 10,000 G for 1 hour. (i) 35 mL of the above dispersion medium was added again, and the same operation was repeated a total of three times. Then, 20 mL of dispersion medium was added and ultrasonic waves were applied for 30 minutes. Next, centrifugation was performed using a centrifuge at 1,500 G for 30 minutes, and the supernatant was collected. Finally, the obtained supernatant was centrifuged using a centrifuge at 10,000 G for 1 hour, the supernatant was discarded, and the MXene dispersion composition was obtained as the remaining precipitate.
[0084] [Comparative Example 3] In Comparative Example 3, the steps of (1) preparation of the precursor (MAX), (2) etching of the precursor, (3) cleaning after etching, (4) Li intercalation, and (5) delamination in Example 6 were carried out to obtain a monolayered MXene-containing clay in an aqueous dispersion medium. This monolayered MXene-containing clay in an aqueous dispersion medium was used to prepare the MXene film described below.
[0085] 〔evaluation〕 The composition samples obtained in Examples 1 to 9 and Comparative Examples 1 to 3 were used to measure the MXene content (solid content) in the composition and to analyze the composition of the surface groups. In addition, the composition samples were used to form MXene films, and the initial electrical conductivity and the change in electrical conductivity over time were determined. Details of each measurement method are given below.
[0086] (Measurement of MXene content in composition) The obtained solvent composition was vacuum-dried at 200° C. for 24 hours, and the solid content (MXene) was calculated based on the weight before and after drying. The results are shown in Table 4 as "MXene content."
[0087] (Composition analysis of surface groups of MXene particles) The composition of the surface groups of the MXene particles was determined by XPS measurement under the following conditions using a VersaProbe X-ray photoelectron spectrometer manufactured by ULVAC-PHI, Inc. The results are shown in Table 4. (XPS measurement conditions) Incident X-ray: monochromatic AlKα X-ray output: 25.6W Measurement area: diameter 100μm Photoelectron capture angle: 45.0 degrees Pass energy: 23.50 eV
[0088] [Preparation of MXene film] The composition obtained in each example was filtered under suction. After filtration, the mixture was dried under vacuum at 200°C for 24 hours to produce an MXene film. A membrane filter (Merck Ltd., Durapore, pore size 0.45 μm) was used for the suction filtration. The supernatant contained 0.05 g of MXene two-dimensional particle solids and 40 mL of pure water. The density and electrical conductivity of the obtained MXene film were measured as follows.
[0089] (Measurement of initial conductivity and σ / σ0 of MXene film) The initial conductivity of the obtained MXene film was determined. First, the surface resistivity was measured at three points per sample, and this was defined as R0 (Ω). To measure the surface resistivity, a simplified low resistivity meter (Loresta AX MCP-T370, manufactured by Mitsubishi Chemical Analytical Co., Ltd.) was used to measure the surface resistance of the film by the four-terminal method. In addition, the thickness (μm) was measured at three points per sample. A micrometer (MDH-25MB, manufactured by Mitutoyo Co., Ltd.) was used to measure the thickness. The volume resistivity was calculated from the above surface resistivity and film thickness, and the initial conductivity (S / cm) was calculated by taking the reciprocal of this value. The average value (σ0) of the initial conductivity at the above three points was used. The results are shown in Table 4.
[0090] In addition, the above MXene film was placed in a sealed desiccator with a small amount of water placed at the bottom so as not to come into direct contact with the water, as in the test apparatus shown in Figure 5c of the literature: Pristine Titanium Carbide MXene Films with Environmentally Stable Conductivity and Superior Mechanical Strength (Adv. Funct. Mater. 2020, 30, 1906996), and kept at room temperature for 7 days in a humid environment saturated with humidity. Then, as described above, the surface resistivity was measured at three points per sample, and the conductivity (S / cm) was calculated from the film thickness. The average value (σ) of the conductivity after 7 days at the above three points was adopted. Then, (σ / σ0) × 100 (%) was calculated as the ratio of the average conductivity (σ) after 7 days to the average initial conductivity (σ0). The results are shown in Table 4. In this embodiment, when (σ / σ0)×100(%) is 70% or more, it is evaluated as having high moisture absorption resistance and high reliability. The (σ / σ0)×100(%) is preferably 80% or more.
[0091] [Table 4]
[0092] The following can be seen from Table 4. That is, the compositions of Examples 1 to 5 according to this embodiment have an MXene content of 1.0 mass% or more and a high dispersion rate, and the conductive films obtained using these compositions have an initial conductivity of 5000 S / cm or more and a conductivity change after 7 days of 70% or more, and can maintain almost the initial conductivity. Furthermore, it is preferable that the modified or terminated T contains a chlorine atom, or that the M of the layer and the PO4 3- , I and SO4 2- In Examples 6 to 9, in which at least one selected from the group consisting of was bonded, the initial conductivity was higher, being 6000 S / cm or more, and the change in conductivity after 7 days was also high, being 85% or more in all cases, and a conductive film with higher moisture absorption resistance was obtained.
[0093] On the other hand, Comparative Example 1 and Comparative Example 2 are examples in which DMSO and DMF were used as the dispersion medium, but in these examples, the dispersibility of the MXene particles was poor and they were in an aggregated state. The initial conductivity of the formed conductive film was quite low, and the conductivity after 7 days also decreased to about half of the initial conductivity. The reason for this is thought to be that the conductive film formed using the composition with poor dispersibility was not dense, and moisture penetrated, causing significant deterioration over time. On the other hand, Comparative Example 3 is an example in which water was used as the dispersion medium. In this example, the initial conductivity was high, but the conductivity after 7 days decreased significantly. The dispersion media DMSO and DMF used in Comparative Example 1 and Comparative Example 2 are organic dispersion media like NMF, but the dispersibility of the MXene particles is clearly different, and this difference in dispersibility also greatly affects the conductivity and moisture absorption resistance (reliability) of the conductive film formed with each composition, and it was found that a conductive film having both excellent conductivity and excellent moisture absorption resistance (reliability) can be obtained by using a composition containing the dispersion medium according to this embodiment.
[0094] The disclosure of this specification may include the following aspects. <1> a conductive two-dimensional particle of a layered material, the particle comprising one or more layers, and a carrier fluid having a dielectric constant greater than that of water; The one or more layers may have the formula: M m X n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 to 4, m is greater than n and less than or equal to 5) and a modification or termination T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, The conductive two-dimensional particle-containing composition, wherein the conductive two-dimensional particle has a fluorine element and an oxygen element. <2> The conductive two-dimensional particle is characterized in that the modification or termination T contains a chlorine atom or the layer M and PO4 3-, I and SO4 2- and at least one selected from the group consisting of <1> 2. A composition comprising the conductive two-dimensional particles according to claim 1 . <3> The dispersion medium having a dielectric constant greater than that of water contains at least one of N-methylformamide and N-methylacetamide. <1> or <2> 2. A composition comprising the conductive two-dimensional particles according to claim 1 . <4> The content of the conductive two-dimensional particles is 1% by mass or more. <1> ~ <3> 2. The conductive two-dimensional particle-containing composition according to claim 1 . <5> Further comprising a polymer, <1> ~ <4> 2. The conductive two-dimensional particle-containing composition according to claim 1 . <6> <1> ~ <5> 2. A conductive film having a conductivity of 5000 S / cm or more, formed from the conductive two-dimensional particle-containing composition according to any one of claims 1 to 11. <7> (a) the formula: M m AX n (wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; A is at least one Group 12, 13, 14, 15, or 16 element; n is 1 to 4, m is greater than n and less than or equal to 5) providing a precursor represented by (b) performing an etching process to remove at least a portion of the A atoms from the precursor using an etching solution; (c) washing the etched product obtained by the etching treatment with water to obtain a water-washed product; (d) performing an intercalation treatment of the intercalation compound, which includes stirring a mixture of the water-washed material and the intercalation compound; (e) forming a composition by using the intercalation treatment product obtained by the intercalation treatment, performing delamination and mixing with a dispersion medium having a relative dielectric constant greater than that of water; A method for producing a conductive two-dimensional particle-containing composition, comprising: <8> In the step (d), the mixture of the water-washed product and the intercalation compound is made alkaline, and In the step (e), the intercalation treatment product is mixed with a dispersion medium having a dielectric constant greater than that of water, and delamination and mixing of the dispersion medium having a dielectric constant greater than that of water are performed simultaneously. <7> A method for producing the conductive two-dimensional particle-containing composition according to claim 1. <9> In the step (d), lithium hydroxide is used as the intercalation compound of the water-washed product. <7> or <8> A method for producing the conductive two-dimensional particle-containing composition according to claim 1. <10> In the step (d), the mixture of the water-washed product and the intercalation compound is acidified, and In the step (e), after the intercalation treatment product is delaminated, the delamination treatment product obtained by the delamination is mixed with a dispersion medium having a relative dielectric constant larger than that of water. <7> A method for producing the conductive two-dimensional particle-containing composition according to claim 1. <11> In the step (d), the mixture of the water-washed product and the intercalation compound is acidified, and In the step (e), the intercalation treatment product is mixed with a dispersion medium having a dielectric constant greater than that of water, and delamination and mixing of the dispersion medium having a dielectric constant greater than that of water are performed simultaneously. <7> A method for producing the conductive two-dimensional particle-containing composition according to claim 1.
[0095] This application claims priority from Japanese Patent Application No. 2021-156888, which is incorporated herein by reference. [Industrial Applicability]
[0096] The conductive two-dimensional particle-containing composition of the present disclosure is useful for forming a conductive film having high initial conductivity and suppressed deterioration of the conductivity over time. The conductive film formed using the conductive two-dimensional particle-containing composition can be used for any suitable purpose, and can be preferably used as an electrode such as an electromagnetic shield (EMI shield), a capacitor electrode, a battery electrode, a biosignal sensing electrode, a sensor electrode, or an antenna electrode. [Explanation of symbols]
[0097] 1a, 1b layer body (M m X n layer) 3a, 5a, 3b, 5b Modified or terminal T 7a, 7b MXene layers 10, 10a, 10b MXene particles (conductive two-dimensional particles, particles of layered materials)
Claims
1. a conductive two-dimensional particle of a layered material, the particle comprising one or more layers, and a carrier fluid having a dielectric constant greater than that of water; The one or more layers may have the following formula: M m X n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. and a modification or terminal T (T is at least one selected from the group consisting of a hydroxyl group, a fluorine atom, a chlorine atom, an oxygen atom, and a hydrogen atom) present on the surface of the layer body, A conductive two-dimensional particle-containing composition, wherein the conductive two-dimensional particles have a fluorine element and an oxygen element.
2. The conductive two-dimensional particle is characterized in that the modification or termination T contains a chlorine atom, or the M of the layer and PO 4 3- , I and SO 4 2- The conductive two-dimensional particle-containing composition according to claim 1 , wherein the conductive two-dimensional particle-containing composition is bonded to at least one selected from the group consisting of:
3. 3. The conductive two-dimensional particle-containing composition according to claim 1, wherein the dispersion medium having a relative dielectric constant greater than that of water contains at least one of N-methylformamide and N-methylacetamide.
4. The conductive two-dimensional particle-containing composition according to claim 1 or 2, wherein the conductive two-dimensional particle content is 1 mass % or more.
5. The conductive two-dimensional particle-containing composition according to claim 1 or 2, further comprising a polymer.
6. A conductive film having a conductivity of 5000 S / cm or more, formed from the conductive two-dimensional particle-containing composition according to claim 1 or 2.
7. (a) a compound of the formula: M m AX n wherein M is at least one Group 3, 4, 5, 6, or 7 metal; X is a carbon atom, a nitrogen atom, or a combination thereof; A is at least one Group 12, 13, 14, 15, or 16 element; n is 1 or more and 4 or less, m is greater than n and is equal to or less than 5. providing a precursor represented by (b) performing an etching process to remove at least a portion of the A atoms from the precursor using an etching solution; (c) washing the etched product obtained by the etching treatment with water to obtain a water-washed product; (d) performing an intercalation treatment of the intercalation compound, which includes stirring a mixture of the water-washed product and the intercalation compound; (e) forming a composition by using the intercalation treatment product obtained by the intercalation treatment, performing delamination and mixing with a dispersion medium having a relative dielectric constant greater than that of water; A method for producing a conductive two-dimensional particle-containing composition, comprising:
8. In the step (d), the mixture of the water-washed product and the intercalation compound is made alkaline; and 8. The method for producing a conductive two-dimensional particle-containing composition according to claim 7, wherein in (e), the intercalation treatment product is mixed with a dispersion medium having a dielectric constant greater than that of water, thereby performing both delamination and mixing of the dispersion medium having a dielectric constant greater than that of water.
9. 9. The method for producing a conductive two-dimensional particle-containing composition according to claim 7 or 8, wherein in (d), lithium hydroxide is used as the intercalation compound of the water-washed material.
10. In the step (d), the mixture of the water-washed product and the intercalation compound is acidified, and 8. A method for producing a conductive two-dimensional particle-containing composition as described in claim 7, wherein in (e), after delamination of the intercalation-treated product is performed, the delamination-treated product obtained by the delamination is mixed with a dispersion medium having a relative dielectric constant greater than that of water.
11. In the step (d), the mixture of the water-washed product and the intercalation compound is acidified, and 8. The method for producing a conductive two-dimensional particle-containing composition according to claim 7, wherein in (e), the intercalation treatment product is mixed with a dispersion medium having a dielectric constant greater than that of water, thereby performing both delamination and mixing of the dispersion medium having a dielectric constant greater than that of water.
Citation Information
Patent Citations
Electrochemical capacitor
WO2018066549A1
Electroconductive composite structure and method for producing same
WO2021131643A1